Microbial growth and physiology: a call for better craftsmanship - Egli, Thomas (Frontiers in Microbiology, 2015)
Virtually every microbiological experiment starts with the cultivation of microbes. Consequently, as originally pointed out by Jacques Monod, handling microbial cultures is a fundamental methodology of microbiology and mastering different cultivation techniques should be part of every microbiologist’s craftsmanship. This is particularly important for research in microbial physiology, as the composition and behaviour of microbes is strongly dependent on their growth environment. It has been pointed out repeatedly by eminent microbiologists that we should give more attention to the media and culturing conditions. However, this is obviously not adhered to with sufficient rigour as mistakes in basic cultivation principles are frequently found in the published research literature. The most frequent mistakes are the use of inappropriate growth media and little or no control of the specific growth rate, and some examples will be discussed here in detail. Therefore, this is a call for better microbiological craftsmanship when cultivating microbial cultures for physiological experiments. This call is not only addressed to researchers but it is probably even more important for the teaching of our discipline.